ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) DALAM PENYAJIAN LAPORAN KEUANGAN PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) GELORA PENDIDIKAN KOTA TOMOHON - Rolos, Renaldy Fernando; Sondakh, Jullie J; Lambey, Robert (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Financial report are a formal report of the financial activities of an entity including a cooperative and prepared as a responsibility of management to internal and eksternal parties. The existing Generally Accepted Accounting Standards are yet a diffifult to be implemented by a cooperative because the existing standards more devoted to a large entities and have aÂ  public accountability . IAI has issued financial Accounting Standards of an entity without Public Accountability or know as SAK ETAP. SAK ETAP is intended to accommodate needs of an entity, wich significantly does not have any accountability, to operate as such Small and Medium Enteprises (SMEs) and a cooperative. This research is aimed to evaluate SAK ETAP implementing in Financial statement of KPRI â€œGelora Pendidikanâ€ Kota Tomohon. KPRI â€œGelora Pendidikanâ€ Kota Tomohon is a cooperative in savings and loans bussiness. Research method are descriptive comparative by comparing primary and secondary data. It is found that a cooperationâ€™s financial report as of 2015 not yet complied with SAK ETAP priciples and a few report have not presented like Cash flow statement and Statement of changes in equity. It is cause by limitied of accounting skills gained by its human resources.Keywords :SAK ETAP, Finacial Statement.